2022
DOI: 10.3390/cells11091463
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Response Inhibitors in Cholangiocarcinoma: Current Progress and Perspectives

Abstract: Cholangiocarcinoma (CCA) is a poorly treatable type of cancer and its incidence is dramatically increasing. The lack of understanding of the biology of this tumor has slowed down the identification of novel targets and the development of effective treatments. Based on next generation sequencing profiling, alterations in DNA damage response (DDR)-related genes are paving the way for DDR-targeting strategies in CCA. Based on the notion of synthetic lethality, several DDR-inhibitors (DDRi) have been developed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“…Importantly, in this study of cell lines, the two IDH1 mutations did not result in an increased GScore, although IDH1 plays a critical role in DNA repair (with α-ketoglutarate being essential for the function of the DNA repair enzyme ALKBH [ 43 ]). The clinical translation of PARP inhibition in CCA is already underway [ 54 ]. It will be paramount to focus the analysis on HRD scores and DDR gene-related defects, given the low correlation we report here for CCA cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in this study of cell lines, the two IDH1 mutations did not result in an increased GScore, although IDH1 plays a critical role in DNA repair (with α-ketoglutarate being essential for the function of the DNA repair enzyme ALKBH [ 43 ]). The clinical translation of PARP inhibition in CCA is already underway [ 54 ]. It will be paramount to focus the analysis on HRD scores and DDR gene-related defects, given the low correlation we report here for CCA cell lines.…”
Section: Discussionmentioning
confidence: 99%
“… 112 These genes include, but are not limited to: BRCA1/2, PALB2, ATM, ATR, RAD51, PTEN, FANCA, FANCAB, MRE11, and ARID1A. 113 In a retrospective study, Spizzo et al investigated 1292 BTC samples and identified BRCA mutations in 3.6% of all cases and noticed that these mutations were associated with a higher rate in subjects with MSI-H (microsatellite instability-high) (19.5 versus 1.7%, p < 0.0001) and tumors with higher tumor mutational burden (TMB), regardless of the MSI status ( p < 0.05). 114 Due to the concept of synthetic lethality, BRCA deficient tumors are sensitive to therapies with PARP inhibitors.…”
Section: Palliative Therapy In Btcmentioning
confidence: 99%
“…DDR pathways encompass a network of signaling cascades and effector mechanisms that maintain genomic integrity and ensure proper cellular responses to DNA damage. Common DDR pathways include the DNA damage sensors (ATM and ATR), signaling kinases (CHK1 and CHK2), DNA repair mechanisms (ARID1A, BRCA, and BAP1), cell cycle regulators (CDKN2A and TP53), and apoptosis induction [109].…”
Section: Stage-dependent Therapeutic Regimesmentioning
confidence: 99%
“…Inhibiting PARP1 in BRCA-mutated CCA can cause a prolonged presence of single-strand breaks, potentially disrupting replication forks and generating double-strand breaks. IDH1/2 mutations have been shown to heighten sensitivity to PARP inhibitors [109,110].…”
Section: Stage-dependent Therapeutic Regimesmentioning
confidence: 99%